Advantages of FDM and gamma irradiation to manufacture personalized medical devices for airway obstructions - Aráoz, Beatriz; Bellía-Munzón, Gastón; Bousquet, Juan I.; Hermida, Élida B. (Frontiers in Bioengineering and Biotechnology, 2023)
Congenital Airway problems such as bronchomalacia (BM) are often life-threatening in the early childhood population. Additive Manufacturing or 3D printing is an innovative technology that makes it possible to build a biomedical device that helps to solve airway obstruction. This work details how a splint for upper airways made of polycaprolactone (PCL) can be fabricated by fusion deposition method (FDM) and sterilized using gamma irradiation. It is presented as a simple, accessible, and cost-reduced alternative that complements other techniques using more expensive and sophisticated printing methods. The morphological and thermomechanical characterization demonstrated that both FDM and sterilization by Gamma irradiation are proper techniques to manufacture splints to solve life-threatening airway obstructions. Moreover, the 3D-printed splints were evaluated by medical staff for their application in a pediatric patient with life-threatening BM. In this regard, the case report of a patient with 34 months of follow-up is presented. Splints manufactured by this affordable 3D printing method successfully surpass breathing arrest in life-threatening airway obstruction in pediatric patients. The success of this procedure represents a fundamental contribution to the treatment of the population in countries where access to expensive and complex technologies is not available.